Biallelic B3GALT6 mutations cause spondylodysplastic Ehlers–Danlos syndrome. (20th June 2018) - Van Damme, Tim; Pang, Xiaomeng; Guillemyn, Brecht; Gulberti, Sandrine; Syx, Delfien; De Rycke, Riet; Kaye, Olivier; de Die-Smulders, Christine E M; Pfundt, Rolph; Kariminejad, Ariana; Nampoothiri, Sheela; Pierquin, Geneviève; et al.
Abstract: Proteoglycans are among the most abundant and structurally complex biomacromolecules and play critical roles in connective tissues. They are composed of a core protein onto which glycosaminoglycan (GAG) side chains are attached via a linker region. Biallelic mutations in B3GALT6, encoding one of the linker region glycosyltransferases, are known to cause either spondyloepimetaphyseal dysplasia (SEMD) or a severe pleiotropic form of Ehlers–Danlos syndromes (EDS). This study provides clinical, molecular and biochemical data on 12 patients with biallelic B3GALT6 mutations. Notably, all patients have features of both EDS and SEMD. In addition, some patients have severe and potential life-threatening complications such as aortic dilatation and aneurysm, cervical spine instability and respiratory insufficiency. Whole-exome sequencing, next generation panel sequencing and direct sequencing identified biallelic B3GALT6 mutations in all patients. We show that these mutations reduce the amount of β3GalT6 protein and lead to a complete loss of galactosyltransferase activity. In turn, this leads to deficient GAG synthesis, and ultrastructural abnormalities in collagen fibril organization. In conclusion, this study redefines the phenotype associated with B3GALT6 mutations on the basis of clinical, molecular and biochemical data in 12 patients, and provides an in-depth assessment of β3GalT6 activity and GAG synthesis to better understand this rare condition.